SARS‐CoV‐2, testosterone and frailty in males (PROTEGGIMI): A multidimensional research project - Salonia, Andrea; Corona, Giovanni; Giwercman, Aleksander; Maggi, Mario; Minhas, Suks; Nappi, Rossella E.; Sofikitis, Nikolaos; Vignozzi, Linda (Andrology (Oxford), 2021)
Preliminary published data depict a much greater prevalence of males with laboratory‐confirmed severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) referred for intensive care unit admission and severe sequelae in several countries. In this context, males seem to not only be more susceptible to the infection compared to female subjects, at least in Western countries, but their case fatality rate attributable to SARS‐CoV‐2 infection is also highest. Therefore, we may speculate that the different hormonal milieu could have a more profound pathophysiological role in association with SARS‐CoV‐2, with endogenous testosterone leaving men more prone to develop more serious complications related to the SARS‐CoV‐2 infection. Another option is that SARS‐CoV‐2 infection per se causes an acute stage of male hypogonadism, the depletion of androgenic action triggering serious or an even fatal course of the disease. Therefore, we strongly advocate the development of a prospective multidimensional andrological translational research project in men, which we called the PROTEGGIMI study. In this Opinion Article, we will not only highlight novel research activity in this area but also invite other researchers and learned scientific societies to join us in our efforts to understand an important and very newly discovered gap in knowledge, which may have serious implications for the lives of millions of men.